Investigation of Measurement Methods of Antioxidant Activity and Involved Mechanisms - Ardestani, Samira Berenji; Sahari, Mohammad Ali (Journal of Pharmacy and Nutrition Sciences, 2013)
Bioactive food components are active ingredients in food or dietary supplements proven to have a role in health and they are safe for human consumption. These compounds exert their antioxidant effects by different mechanisms such as hydrogen atom transfer (HAT) or single electron transfer (SET) and their efficiencies can be evaluated by several methods such as ferric reducing ability of plasma (FRAP), trolox equivalent antioxidant capacity (TEAC), dipheny-picrylhydrazil (DPPH), Folin-Ciocaltue method (FCM), etc. In this review, these mechanisms and methods will be discussed in details.